Navigating offshoring supply chain management decisions between cost advantages and corporate social responsibility risk. (26th July 2022) - Zeisel, Stefan; Peter, Moritz
In the globalised world, companies would source major parts of their production, mainly for economic reasons, from low-cost countries. Therefore, it is important to understand implicit corporate social responsibility (CSR) risk when making offshoring decisions. This article presents a transparent composite index of CSR risk for a list of 170 countries. Combining the country CSR index with GDP per capita can help firms identify attractive offshoring destinations with relatively low CSR risk. This innovative approach allows companies to reconcile CSR considerations with economic success when designing international supply chains.